2x (x+1)=x(x+5)+3(12-x)
Alguém pode me ajudar ?!
Soluções para a tarefa
Respondido por
20
2x (x+1)=x(x+5)+3(12-x)
2x² + 2x =x² + 5x + 36 - 3x
2x² - x² + 2x - 5x + 3x - 36 = 0
x² - 3x + 3x - 36 = 0
x² - 36 = 0
x² = 36
x=± √36
x= ± 6
S= ( + 6, - 6)
2x² + 2x =x² + 5x + 36 - 3x
2x² - x² + 2x - 5x + 3x - 36 = 0
x² - 3x + 3x - 36 = 0
x² - 36 = 0
x² = 36
x=± √36
x= ± 6
S= ( + 6, - 6)
lola101:
Obrigada
Respondido por
8
Olá!
![2x(x + 1) = x(x + 5) + 3(12 - x) \\ 2 {x}^{2} + 2x = {x}^{2} + 5x + 36 - 3x \\ 2 {x}^{2} - {x}^{2} + 2x - 5x + 3x = + 36 \\ {x}^{2} = 36 2x(x + 1) = x(x + 5) + 3(12 - x) \\ 2 {x}^{2} + 2x = {x}^{2} + 5x + 36 - 3x \\ 2 {x}^{2} - {x}^{2} + 2x - 5x + 3x = + 36 \\ {x}^{2} = 36](https://tex.z-dn.net/?f=2x%28x+%2B+1%29+%3D+x%28x+%2B+5%29+%2B+3%2812+-+x%29+%5C%5C+2+%7Bx%7D%5E%7B2%7D+%2B+2x+%3D+%7Bx%7D%5E%7B2%7D+%2B+5x+%2B+36+-+3x+%5C%5C+2+%7Bx%7D%5E%7B2%7D+-+%7Bx%7D%5E%7B2%7D+%2B+2x+-+5x+%2B+3x+%3D+%2B+36+%5C%5C+%7Bx%7D%5E%7B2%7D+%3D+36)
x = ± √36
x = ± 6
S = {- 6, + 6}
Espero ter ajudado! :)
x = ± √36
x = ± 6
S = {- 6, + 6}
Espero ter ajudado! :)
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás